Correlation of hair and plasma efavirenz concentrations in HIV-positive South Africans - Johnston, Jenna (South Afr J HIV Med, 2019)
BACKGROUND: Antiretroviral concentrations in hair provide a longer window of drug detection and are useful for measuring longer-term drug exposure. Efavirenz is an important component of first-line treatment in resource-limited settings, but its concentrations in hair have not been well studied. METHODS: This study is a supplementary to a randomised controlled trial of an adherence intervention using an electronic adherence measuring device. Hair and plasma samples were collected from human immunodeficiency virus-positive patients in Cape Town, South Africa. Previously validated liquid chromatography tandem mass spectrometry methods were used to measure efavirenz concentrations in the collected hair and plasma samples. CYP2B6 genotyping of participants was also performed. Data analysis was performed using descriptive and comparative statistics as well as regression modelling. RESULTS: Hair samples were collected from 59% of patients enrolled in the parent study. Results indicated that hair efavirenz concentrations were significantly influenced by participants’ CYP2B6 metaboliser status. Median efavirenz concentrations for extensive, intermediate and slow metaboliser genotypes were 3.54 ng/mg, 5.11 ng/mg and 10.66 ng/mg, respectively. A strong correlation was observed between the efavirenz concentrations measured in hair and plasma samples (Spearman’s correlation coefficients, 0.672–0.741, p < 0.0001). No relationship between hair efavirenz concentrations and virological failure or adherence measured using an electronic adherence was shown. CONCLUSION: The results from this study provide further insight into the potential of using hair as a matrix for measuring antiretroviral concentrations. However, challenges experienced in collecting hair samples suggest that this adherence measure may have limited utility in an African population.